CAT Scan: A Critical Review of the Critical-Thinking Assessment Test - Possin, Kevin (Informal Logic, 2020)
The CAT is entirely dedicated to assessing the critical-thinking skills involved in scientific reasoning and practical problem solving. While the test is found to have reasonable content validity, various issues with its prompts are discussed, along with significant issues with its scoring. The CAT’s recommended use as a “model” for curricular changes, called CAT Apps, is criticized as “teaching to the test.”